We can Diagnose it if we Consider it. Diagnostic Pitfall for Placenta: Placental Mesenchymal Dysplasia - Havva Serap TORU; Esra ÇOBANKENT AYTEKİN; Cem Yaşar SANHAL; Sezin YAKUT; Zafer ÇETİN; İbrahim İnanç MENDİLCİOĞLU; Hadice Elif PEŞTERELİ (Federation of Turkish Pathology Societies, 2018)
Placental mesenchymal dysplasia is an increasingly recognizable abnormality. Early cases have been confused with partial hydatidiform mole. Placental mesenchymal dysplasia is probably under-diagnosed because of being an unfamiliar clinical entity and also mistaken for gestational trophoblastic disease due to the similar sonographic findings of two entities. In this report, we describe the clinical, gross, and histopathological findings of placental mesenchymal dysplasia in two cases. The 33-week-preterm baby of a 26-year-old woman with cardiovascular disease and 342 gram placenta and the 19-week fetus with trisomy 21 of a 40 year-old woman were terminated. Macroscopically thick-walled vessels and microscopically hydropic villous with peripherally localized thick-walled vessels without trophoblastic cell proliferation were observed in both cases. These two cases represent a rare placental anomaly that is benign but it is challenging to distinguish placental mesenchymal dysplasia from an incomplete mole. Placental mesenchymal dysplasia should be included in the differential diagnosis of sonographic findings that show a normal appearing fetus and a placenta with cystic lesions. Placental mesenchymal dysplasia is associated with pregnancy-related hypertension. In conclusion, the most important point is "you can diagnose it if you consider it".